Model Pengelolaan Lingkungan Tambak Udang Vaname Berkelanjutan di Pesisir Kabupaten Situbondo - Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2025)
Vannamei shrimp (Litopenaeus vannamei) aquaculture is a leading sector in the coastal area of Situbondo Regency, contributing significantly to the local economy but posing environmental challenges. This study aims to develop a sustainable environmental management model for vannamei shrimp ponds based on empirical data and literature review. A descriptive–qualitative approach was used by synthesizing secondary data from DKP Situbondo, SBPS, and previous studies on water quality, socio-economics, and institutional governance. Results show that pond waste load has approached the environmental carrying capacity (ratio 0.78), with average ammonia concentration of 0.33 mg/L in intensive systems. About 65% of shrimp farmers are small-scale with limited access to capital and technology. Institutional strengthening, cross-sectoral coordination, and eco-friendly innovations such as biofloc, water recirculation, and phytoremediation are essential. The proposed model emphasizes multi-stakeholder collaboration, ecosystem integration, and technological innovation to balance pond productivity with coastal environmental sustainability in Situbondo. Vannamei shrimp, environmental management, sustainable ponds, Situbondo, coastal.